The Effectiveness of E-booklet Ungaran Mountain Natural Dyeing Plants as A Supplement for Angiosperm Sub Matter to Improve Student’s Scientific Literacy Abilities - Hidayat, Muhammad Syarif; Rahayu, Enni Suwarsi; Rahayuningsih, Margareta (Unnes Science Education Journal, 2024)
Biology learning media is needed in school learning, so Biology teachers must prepare for the media needs. One material that requires additional learning media is plant material. The learning media is expected to complement the books used in schools. This research aims to: 1) Identify types of natural dye plants on Mount Ungaran, especially Ngesrepbalong Village, Limbangan District, Kendal Regency. 2) Analyzing the effectiveness of E-booklets in increasing students’ scientific literacy on Plantae material. 3) Analyze the practicality of E-booklets as a learning medium for Plantae material. The method of data collection techniques use interviews, observation, and questionnaires. The analysis data used N-gain. Based on the results of analysis and research, it shows: 1) There are 19 species of natural dye plants identified on Mount Ungaran, especially in Ngesrepbalong Village, Limbangan District, Kendal Regency. 2) E-booklets are effectively used in biology learning. 3) E-booklets are practically used in biology learning. The results of this research can be used as a reference for developing other media in learning Plantae material.